2019
DOI: 10.1080/15470148.2019.1640819
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of stakeholders in small-scale sporting events

Abstract: Small-scale events represent an important asset for the development of tourist destinations. As local stakeholders play a major role in conceptualizing and developing small-scale events, this study sheds light upon stakeholders' perceptions toward such events. The current study was carried out through qualitative interviews based on the case of the FIS (International Ski Federation) World Junior Alpine Ski Championships 2019. The findings of this study reveal that for small-scale event success, the involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 55 publications
(94 reference statements)
1
17
0
Order By: Relevance
“…Inspired by recent research [4] which examined, in a pre-event perspective, the role of stakeholders in a small-scale sports event, and based on the results, this article intends to demonstrate that from a residents' perspective, a small-scale sports event can represent an opportunity to reflect upon and plan for sustainable development at a tourism-led destination, now and in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by recent research [4] which examined, in a pre-event perspective, the role of stakeholders in a small-scale sports event, and based on the results, this article intends to demonstrate that from a residents' perspective, a small-scale sports event can represent an opportunity to reflect upon and plan for sustainable development at a tourism-led destination, now and in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Sport can also play a decisive role in the realm of sustainable development by adopting in particular policies aimed at paying greater attention to the environment [3]. The author presents a descriptive analysis of a small-scale sports event, taking into consideration a case already analyzed ex ante by the author in a previous study [4]. There is still a clear research gap in the various areas of analysis for small-scale events from a local perspective, given that many studies have chiefly focused on the economic impact [5].…”
Section: Introductionmentioning
confidence: 99%
“…Sports event literature has delivered a range of issues organizing committees have to deal with during the scheduling of an event, as shown by Parent and Deephouse (2007). Other examples analyzing different stakeholders' perspectives in the context of sports events were provided by Bazzanella, Peters, and Schnitzer (2019) and Peters and Schnitzer (2015), who assessed expectations, experiences, and (social) legacies as perceived by stakeholders (Reid, 2011). Literature on stakeholders in the context of international sports events has shown that scientific knowledge of perceived experiences is scarce, especially that considering co-creation activities of stakeholders in sports events and customer experience patterns of the respective stakeholders.…”
Section: Stakeholder Theory and Sports Eventsmentioning
confidence: 99%
“…Major events draw significant economic and marketing benefits that contribute to the success of the destination brand in the long run (Bazzanella et al, 2019). Jago et al (2003) note the importance of the longevity/tradition of an event for a destination when seeking branding opportunities.…”
Section: The Influence Of Sport Tourism Events On Destination Brandsmentioning
confidence: 99%
“…It is from this backdrop that this paper investigates the perceptions of event attendees at two major sporting events in South Africa on perceived brand messages that influence travel experiences. Since local stakeholders play a major role in conceptualising and developing major events (Bazzanella, Peters, & Schnitzer, 2019), the study sheds light on stakeholder perceptions towards the utilisation of major events as destination brand promoters. The focus on South Africa is motivated by the fact that the country is still categorized as a developing destination brand, yet newly transitioned from an old (apartheid) image (Swart, Moyo, & Hattingh, 2019), which therefore marks this particular destination as an interesting case study context for exploring brand perceptions and tourism experiences.…”
Section: Introductionmentioning
confidence: 99%